Modelling hereditary diffuse gastric cancer initiation using transgenic mouse‐derived gastric organoids and single‐cell sequencing. Issue 3 (12th May 2021) - Dixon, Katherine; Brew, Tom; Farnell, David; Godwin, Tanis D; Cheung, Simon; Chow, Christine; Ta, Monica; Ho, Germain; Bui, Minh; Douglas, J Maxwell; Campbell, Kieran R; El‐Naggar, Amal; et al.
Abstract: Hereditary diffuse gastric cancer (HDGC) is a cancer syndrome caused by germline variants in CDH1, the gene encoding the cell–cell adhesion molecule E‐cadherin. Loss of E‐cadherin in cancer is associated with cellular dedifferentiation and poor prognosis, but the mechanisms through which CDH1 loss initiates HDGC are not known. Using single‐cell RNA sequencing, we explored the transcriptional landscape of a murine organoid model of HDGC to characterize the impact of CDH1 loss in early tumourigenesis. Progenitor populations of stratified squamous and simple columnar epithelium, characteristic of the mouse stomach, showed lineage‐specific transcriptional programs. Cdh1 inactivation resulted in shifts along the squamous differentiation trajectory associated with aberrant expression of genes central to gastrointestinal epithelial differentiation. Cytokeratin 7 (CK7), encoded by the differentiation‐dependent gene Krt7, was a specific marker for early neoplastic lesions in CDH1 carriers. Our findings suggest that deregulation of developmental transcriptional programs may precede malignancy in HDGC. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.